Intake of Scrophularia buergeriana extract (Brainon®) shows memory improvement effects in a randomized, double-blind, placebo-controlled clinical study: Memory improvement effect of Brainon® - Lee, sung-kwon; Kim, Hae-Lim; Park, Seong-Hyeon; Choi, Bong-Keun; Lee, Dong-Ryung; Yang, Seung-Hwan (Progress in Nutrition, 2024)
Background and aim: Scrophularia buergeriana (SB), also known as Hyun-Sam in Korea, is a traditional medicine used to alleviate fever, swollen skin, constipation, and other health issues. The aim of this study was to evaluate the efficacy and safety of Scrophularia buergeriana 70% ethanol extract (Brainon®) supplementation on memory improvement in adults who complained of memory impairment. Methods: Eighty volunteers were recruited from Wonkwang University, Korean Medicine Hospital in Iksan, Republic of Korea. Participants were given either a daily dose of 300 mg of Brainon® or a placebo. In this study, the Korean Mini-Mental State Examination (K-MMSE), a Computerized Neurocognitive function Test (CNT), Digit Span Test, serum Brain-Derived Neurotrophic Factor (BDNF), and interleukin-6 (IL-6) were used to check effects of Brainon® on memory function in those with mild memory impairment. Results: Consumption of Brainon® resulted in significant improvements in immediate recall total score of the CNT-Verbal learning test, correct response and omission error items of the CNT-Visual C.P.T, backward recall of the Digit span test, and serum levels of BDNF and IL-6. Clinically significant adverse events or physical changes were not observed in this study. Conclusions: This clinical trial demonstrated for the first time the efficacy and safety of SB extract (Brainon®) in enhancing memory function. The results of this study indicate that consumption of Brainon® could lead to an improvement in memory without any adverse effects. Based on these research findings, Brainon® is expected to be developed as a health functional food ingredient.